ANALISA PENGARUH KEBERHASILAN PROGRAM 21 HARI SIKAT GIGI TERHADAP STANDAR ORAL HIGIENE INDEX SYMPLIFIED (OHIS) PADA PESERTA DIDIK SEKOLAH DASAR NEGERI 084087 KOTA SIBOLGA TAHUN 2020 - Lisbet Masniati Sitinjak (Jurnal Kajian Kesehatan Masyarakat, 2022)
WOHD launched a 21-day toothbrush program after breakfast and before bedtime. Data shows that 80% of Indonesians have dirty and perforated teeth and periodontal support tissue for various reasons. (Yuliana,2015) The purpose of this study was to see the effect of the success of the 21-day toothbrush program (P21HSG) on the Oral Hygiene IndexSimplified (OHIS) Standard on oral hygiene and student behavior at Public Elementary School (SDN) 084087 Sibolga City in 2020. This type of research is quasi experiment design. This research uses lecture method and P21HSG method. Pre and post test group design, that is. The sample was grade 4 elementary school students as many as 40 people divided into groups, namely 20 control groups and 20 case groups. Samples were taken by purposive sampling method. Data collection was conducted using behavioral questionnaires and OHIS scores. The results showed an increase in student behavior score after lecture method counseling by 1.45 and in lecture method and P21HSG by1.80. There was a decrease instudents' OHIS score after lecture method counseling by 2.05 and in lecture method and P21HSG by 2.65. There is an effect of P21HSG success on OHIS Standard on oral hygiene and student behavior at SDN 084087 Sibolga City 2020, p< α (0.05). Ongoing efforts need to be carried out so that elementary school students can maintain good oral and dental health properly, providing counseling on oral and dental health and P21HSG.